Lean mass, muscle strength, and muscle quality in retired rugby players: The UK rugby health project - Entwistle, I.; Francis, P.; Lees, M.; Hume, P.; Hind, K. (International Journal of Sports Medicine, 2022)
Although athletes from sports such as rugby have greater lean mass and strength during their playing careers, little is known about these characteristics post-retirement. Therefore, this study investigated lean mass, strength, and muscle quality in retired elite and amateur rugby players and non-contact athletes. Retired elite male rugby players (n=42, 43.9±10.3 y; 101.1±13.4 kg; 1.82±0.09 m), amateur rugby players (n=46, 48.0±10.5 y; 98.9±16.6 kg; 1.79±0.07 m) and non-contact athletes (n=30, 51.3±12.5 y; 91.3±13.4 kg; 1.79±0.07 m) received one total body dual-energy X-ray absorptiometry assessment of appendicular lean mass (ALM) and ALM index (ALMI). Grip strength was measured, and muscle quality (grip strength/unit of arm lean mass) was calculated. Sarcopenia was identified as ALMI<7.23 kg/m2 and handgrip strength<37.2 kg. Total lean mass, ALM and grip strength were greater in the elite rugby compared to amateur rugby and non-contact groups (p<0.01). There were no significant differences in muscle quality or sarcopenia prevalence. Retired elite rugby players had greater lean mass and grip strength than amateur rugby and non-contact athletes, although muscle quality was similar. The greater lean mass and strength might reflect genetic influences or previous participation in a highly physical sport.